Soil Salinity and Sodicity in Drylands: A Review of Causes, Effects, Monitoring, and Restoration Measures - Stavi, Ilan; Thevs, Niels; Priori, Simone (Frontiers in Environmental Science, 2021)
Soil salinization and sodification are common processes that particularly characterize drylands. These processes can be attributed either to natural conditions or anthropogenic activities. While natural causes include factors such as climate, lithology, topography, and pedology, human causes are mostly related to agricultural land-use, and specifically, to irrigated agriculture. The objective of this study was to thoroughly review this topic, while highlighting the major challenges and related opportunities. Over time, the extent of saline, sodic, and saline-sodic croplands has increased, resulting in accelerated land degradation and desertification, decreased agricultural productivity, and consequently jeopardizing environmental and food security. Mapping and monitoring saline soils is an important management tool, aimed at determining the extent and severity of salinization processes. Recent developments in advanced remote sensing methods have improved the efficacy of mapping and monitoring saline soils. Knowledge on prevention, mitigation, and recovery of soil salinity and sodicity has substantially grown over time. This knowledge includes advanced measures for salt flushing and leaching, water-saving irrigation technologies, precision fertilizer systems, chemical restoration, organic and microbial remediation, and phytoremediation of affected lands. Of a particular interest is the development of forestry-related means, with afforestation, reforestation, agroforestry, and silvopasture practices for the recovery of salt-affected soils. The forecasted expansion of drylands and aggravated drying of existing drylands due to climatic change emphasize the importance of this topic.